ANALISIS IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA APLIKASI CANDIL - Rani Supartini; Angga Hadiapurwa (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
This article discusses the implementation of CRM in West Java Dispusipda. CRM in the library is very effective to do, because the main focus of the library is the user. The research method used in this article is a qualitative research method. The results of the analysis carried out are the implementation of CRM on the Candil application by providing interesting features, namely giving appreciation, requesting books, and bookshelves. It aims to achieve user satisfaction, which based on the analysis of the assessment of the Play Store application shows a good category.